"THE REPRESENTATION OF WOMEN AND INNER EMOTIONAL STATES IN POETRY: A STUDY OF THE WORKS OF H. KHUDOYBERDIYEVA, N. AFOQ, AND Q. RAHIMBOYEVA" - Berdieva Dilnavoz Orif qizi (Bright Mind Publishing, 2025)
This article explores how the inner emotional states of women are represented in the poetic works of three prominent Uzbek poets: Halima Khudoyberdiyeva, Nodira Afak, and Kutlibeka Rahimboyeva. Through a close textual analysis of selected poems, the paper reveals recurring themes of feminine identity, emotional resilience, spiritual longing, and social introspection. The study highlights the poets' unique use of metaphors, symbols, and poetic voice in portraying the lived emotional experiences of women within the cultural and historical context of Uzbekistan.
Keywords: women in poetry, emotional representation, Uzbek literature, H. Khudoyberdiyeva, N. Afoq, K. Rahimboyeva, feminine identity, metaphor